Storytelling: Alternatif Media untuk Penanaman Pendidikan Karakter pada Siswa - Syamsurrijal, Arif; Rahman, Tatang Aulia (Institut Agama Islam Al-Hikmah Tuban, 2020)
In the level of children's intelligence is not the only thing that needs to be improved, but character education also needs to be instilled in the minds of everychild. This is because currently children live in the midst of the incessant use of technology and media. There are various ways or media that can be used to teach or implant character education in children, one of which is using storytelling. By telling a story to children, children will feel entertained, and indirectly the stories read convey noble values that will be embedded in the minds of students. Indonesia has enough folklore that can be used as material for storytelling. In addition, teachers can also choose a variety of stories from the prophets, scholars, and Muslim scholars to be known by children as well as children are able to take good character values for them. Because these values will become their provisions to face the times. Keyword. character education, children and storytelling